2012
DOI: 10.1038/gim.2012.47
|View full text |Cite
|
Sign up to set email alerts
|

Genetic testing for inherited heart diseases: longitudinal impact on health-related quality of life

Abstract: Purpose: A genetic diagnosis is an extremely useful tool in the management and care of families with inherited heart diseases, particularly in allowing clarification of risk status of asymptomatic family members. The psychosocial consequences of genetic testing in this group are poorly understood. This longitudinal pilot study sought to determine changes in health-related quality of life in patients and asymptomatic family members undergoing genetic testing for inherited heart diseases.methods: Individuals att… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(12 citation statements)
references
References 28 publications
1
11
0
Order By: Relevance
“…2 Psychological problems in patients with a clinical diagnosis of a genetic heart disease have been described before, and we also know that healthy relatives who are carriers of the genetic predisposition for such diseases show no, or only temporary, psychological impairment in the first months after hearing their genetic test result. [3][4][5][6][7][8][9] The results on psychological wellbeing shown by Yeates et al and previously by other researchers are intuitively correct. Of course you feel miserable when a close relative dies prematurely or when you have a disease that poses a greater risk of dying young.…”
supporting
confidence: 67%
“…2 Psychological problems in patients with a clinical diagnosis of a genetic heart disease have been described before, and we also know that healthy relatives who are carriers of the genetic predisposition for such diseases show no, or only temporary, psychological impairment in the first months after hearing their genetic test result. [3][4][5][6][7][8][9] The results on psychological wellbeing shown by Yeates et al and previously by other researchers are intuitively correct. Of course you feel miserable when a close relative dies prematurely or when you have a disease that poses a greater risk of dying young.…”
supporting
confidence: 67%
“…The goal of genetic counseling is to support patients in understanding and adapting to the medical, psychosocial, and familial implications of hereditary conditions, including providing thorough discussions about risks, benefits, and options available for clinical and/or genetic testing 29,30 . Patients make important decisions about genetic testing based on a number of determinants, including cost, insurance coverage, and perceived medical and psychosocial benefit of testing for self and family members.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies of women who have undergone breast cancer genetic testing reported more intrusive thoughts, avoidance, and cancer distress with positive results in unaffected women, indicating that experiences depend on clinical context (Lumish et al 2017). Studies analyzing the quality of life (QoL) of patients who had cardiogenetic testing have found that the experience of genetic testing and type of genetic test results were not associated with a difference in QoL, rather differences in QoL are associated with symptoms (Christiaans et al 2009;Ingles et al 2012). Though in one study, patients with positive results had higher bodily pain scales (Hickey et al 2014).…”
Section: Introductionmentioning
confidence: 99%